PENGENALAN BUDAYA JEPANG BELA DIRI AIKIDO DI SDN 11 DAUH PURI DENPASAR-BALI - Wayan Nurita; Ladycia Sundayra (LOKATARA SARASWATI, 2024)
Teaching and learning activities at SD Negeri 11 Dauh Puri Denpasar apart from focusing on academic activities, also carry out non-academic activities such as arts and sports. The implementation of non-academic activities is still considered less than optimal due to the lack of supporting human resources so that students have a lot of free time. With space to fill arts, culture and sports activities, the Japanese Literature Study Program PKM team carried out a program related to Japanese culture, namely the traditional Japanese martial art, Aikido. It is considered good to introduce Aikido to elementary school students because apart from having elements of martial arts, it also has elements of art and culture. Aikido is a type of self-defense with empty hand techniques in the form of locks, throws, attacks, defenses, defenses both in standing and sitting positions. Apart from that, there are also techniques for using weapons in the form of wooden swords, wooden sticks and wooden knives. Aikido, which is a martial arts sport, is important to introduce to students at SDN 11 Dauh Puri because apart from physical training, it is also mental training. The aim of this PKM activity is to fill students' free time on Saturdays with Aikido training for physical, mental training and introduction to foreign cultures. Aikido martial arts does not only emphasize physical attitude, but also a strong spirit to balance their academic and non-academic skills to continue their education at a higher level.